Medical students' knowledge, attitude, and practice regarding hepatitis B and C virus infections in Jordan: A cross‐sectional study - Husam Abu Suilik; Osama Alfaqeh; Abdalqader Alshrouf; Omnia M. Abdallah; Jehad Feras AlSamhori; Lujain Lataifeh; Mohammad Alsbou; Mohammad Abusuilik; Nawar Khalil; Mohand Odeh; Hashem Abu Serhan; Abdulqadir J. Nashwan; et al. (Health Science Reports, 2024)
Abstract Background and Aims We aimed to assess the levels of hepatitis B and C knowledge, attitudes, and practices among medical students in Jordan. A survey included participation from medical students across all faculties in Jordan, from 2022 to 2023. Methods The data were analyzed with The R Statistical Software (v4.1.2; R Core Team 2022) using descriptive statistics, and multivariate regression analyses. A p ≤ 0.05 was considered statistically significant. Results In this study of 2602 participants, the average age was 21.4, with 52.6% females. Most were fourth‐year medical students (19.1%), and 52.3% were in clinical years. The mean knowledge score was 14 (SD ± 2.5) out of 20, categorized as high at 58.84%, and low at 41.16%. The mean practice score was 4.89 (SD ± 1.1) out of 7, with good practice in 65%, and low in 35%. The mean attitude score was 1.6 (SD ± 3.1), categorized as low in 81.7%, and high in 18.3%,. High levels of KAP were associated with gender, year of study, and university. Male respondents had lower knowledge (OR: 0.73; p: 0.001; 95% CI: −0.50 to −0.13), and students in the first to fifth years scored lower than sixth‐year students. There were moderate positive associations between knowledge and attitude (r: 0.33, p < 0.001), and weak positive associations between knowledge and practice (r: 0.17, p < 0.001), and attitude and practice (r: 0.133, p < 0.001). Conclusion In conclusion, the participants revealed high adherence to some practices and intermediate knowledge levels. Gender, academic year, and university affiliation emerged as significant factors, highlighting the necessity for tailored interventions.